Properties Of Gold Nanoparticles And Its Conjugation With Biomolecules For Diagnostic Application - Makhsin, Siti Rabizah (2013)

(untitled)
In this study, colloidal gold nanoparticles (AuNPs) were synthesized using the seeding-growth method. This approach was beneficial to produce spherical shape AuNPs with the size range from 6 nm to 150 nm with polydispersity index (PDI) below 0.2 by varying the volume of seed solution. AuNPs synthesized using this method also are readily available for conjugation and require lower antibody concentration (~50% less) when applied to the immunochromatographic (ICG) strip assay compared to conventional method, thus significantly reduce the ICG strip production cost. Sodium borohydride and trisodium citrate were used as reducing agent to obtain 4 nm – 40 nm AuNPs seeds. The optimum concentration of hydroxylamine as a reducing agent at the growth stage was 0.1 to 0.2 M. High concentration of AuNPs solution with tunable size (35 nm – 90 nm) with the degree of ellipticity (G)  1.09 was obtained when volume of gold chloride were tuned from 0.25 ml to 3 ml. Selected sizes of AuNPs (10 nm and 40 nm) were then successfully conjugated to biomolecules and proved to work well as detector on ICG strip assay. The properties of AuNPs (sizes: 20, 30 and 40 nm) synthesized using the citrate reduction and seeding-growth methods and their conjugation to mouse anti-human IgG4 (MHIgG4) to detect Brugian filariasis disease using ICG strip assay were compared. The 30 nm AuNPs-MHIgG4 with optical density (OD) 4 from the seeding-growth method showed the best performance for use in labelling ICG strips assay since it displayed the best sensitivity and the highest specificity when tested with serum samples from Brugian filariasis patients and controls.